High rate algal systems for treating wastewater: a comparison - Kube, Matthew; Fan, Linhua; Roddick, Felicity; Whitton, Rachel; Pidou, Marc; Jefferson, Bruce (Elsevier, 2022)
Algal systems can remove nitrogen (N) and phosphorus (P) from wastewater while producing valuable biomass. The microalga Chlorella vulgaris in three concentrated forms (suspended, entrapped in Ca-alginate gel beads and as a biofilm on supports and the macroalga Oedogonium cardiacum were compared for treating secondary effluent containing 15 mg/L of ammonium (N-NH4+), 6 mg/L of nitrate (N-NO3−), and 7 mg/L of total phosphorus (TP) with a hydraulic retention time of 12 h. Identical conditions and reaction vessels enabled a direct comparison of growth systems. The biofilm system was the most effective of the microalgal systems, decreasing concentrations to 1.9 mg/L TP and 0.5 mg/L N-NO3− on average from day 3 to 24, and like the other microalgal systems, was not as effective for N-NH4+ removal (average of 9.0 mg/L). The macroalgal system decreased TP to 1.3 mg/L and N-NH4+ to ≤0.5 mg/L on average from day 16 to 30 and operated for longer than the other systems, but was not effective for N-NO3− removal (average of 4.8 mg/L). Hence the minimum TN concentration of the effluent from the macroalgal system (7.1 mg/L) was lower than for the biofilm system (10.6 mg/L) from the feed of 24 mg/L. The biofilm system produced 56 mg/L/d and the macroalgae 102 mg/L/d of biomass. The production of the highest quality effluent for longer and of more biomass than the microalgal systems, combined with their larger cell size which facilitates reactor operation, demonstrates that macroalgae can compete with microalgae for wastewater remediation.
Keywords: Microalgae; Macroalgae; Biofilm; Immobilisation; Wastewater treatment; Biomass production